2018
DOI: 10.1007/978-3-319-92108-2_12
|View full text |Cite
|
Sign up to set email alerts
|

A Social Companion and Conversational Partner for the Elderly

Abstract: In this work, we present the development and evaluation of a social companion and conversation partner for the special user group of elderly. With the aim of designing a user-adaptive system, we responded to the desires of the elderly which have been identified during various interviews and created a companion which talks and listens to the elderly users. Moreover, we conducted a user study with a small group of retired seniors living at home or in a nursing home. The results show that our companion and its di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…The study further suggested that the social acceptance of a social robot increases when the robot can comprehend the very needs of its user and act according to the situation [62]. Results of the human study in [63] verified the fact that humans prefer user-adaptive dialogs while having a conversation even with a robot companion. Work proposed in [64] is an encouraging example for the growing harmony between humans and robots that are emotionally intelligent, as stated above.…”
Section: B Modern Developmentsmentioning
confidence: 65%
“…The study further suggested that the social acceptance of a social robot increases when the robot can comprehend the very needs of its user and act according to the situation [62]. Results of the human study in [63] verified the fact that humans prefer user-adaptive dialogs while having a conversation even with a robot companion. Work proposed in [64] is an encouraging example for the growing harmony between humans and robots that are emotionally intelligent, as stated above.…”
Section: B Modern Developmentsmentioning
confidence: 65%
“…It is certain that robotics technology can play a significant role to support older persons to perform their activities of daily living independently. Application of assistive social robots to facilitate the needs of older persons becoming widespread and extensively studied [139][140][141][142][143][144][145][146][147]. However, introducing robotics technology to older persons and requesting them to deploy the solution can be challenging.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it is found that the social acceptance of a service robot increases when a robot is able to perceive the very needs of a user and act accordingly [ 26 ]. Results of the human study in [ 27 ] verify that humans prefer user adaptive dialogs in conversations even with a robot. The work explained in [ 28 ] is a promising example of the growing rapport between humans and robots with such an intelligence.…”
Section: Related Workmentioning
confidence: 99%